Empowering your pupils through role-play : - Morales, Rosanna (Routledge, 2008)
Empowering Your Pupils through Role-play reveals the power of role-play in creating a safe space for students to explore emotions and build resilience through performance, discussion and the sharing of ideas, whilst enabling teachers to meet curriculum outcomes.